Lean model-based definition framework for product life cycle - Goher, Kamran (Cranfield University, 2019)
Poster presented at Cranfield University’s 2019 Manufacturing Doctoral Community event.
Keywords: MBD; model based enterprise; product lifecycle; MDC19 poster; Innovation and Technology Management